2013
DOI: 10.1016/j.jcrc.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between age and use of intensive care among surgical Medicare beneficiaries

Abstract: Purpose To determine the role age plays in use of intensive care for patients who have major surgery. Materials and Methods Retrospective cohort study examining the association between age and admission to an intensive care unit (ICU) for all Medicare beneficiaries aged 65 or older who had a hospitalization for one of five surgical procedures: esophagectomy, cystectomy, pancreaticoduodenectomy (PD), elective open abdominal aortic aneurysm repair (open AAA), and elective endovascular AAA repair (endo AAA) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This dataset contains data on all Medicare hospitalizations from 2004 through 2008, linked with data from the American Hospital Association annual survey from 2007. 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset contains data on all Medicare hospitalizations from 2004 through 2008, linked with data from the American Hospital Association annual survey from 2007. 13…”
Section: Methodsmentioning
confidence: 99%
“…We included all patients 65 years or older undergoing five select surgical procedures during a hospitalization, and excluded Medicare beneficiaries under age 65 since they represent a highly selected group of individuals with specific diagnoses, as previously described. 13 The procedures were: elective endovascular repair of abdominal aortic aneurysm (endovascular AAA), cystectomy, pancreaticoduodenectomy (PD), esophagectomy, and elective open repair of an abdominal aortic aneurysm (open AAA). We chose these surgical procedures from a larger list of possible procedures after initial inspection of the data because they are 1) commonly performed in patients over the age of 65, 2) well circumscribed and usually not associated with another surgery, and 3) associated with a range of different hospital mortality rates (see Supplemental Digital Content Table 1, listing individual ICD-9-CM and procedure codes used).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Older people require more medical services than younger people because of the higher rates of functional impairment and chronic morbidity. [1][2][3][4] Consequently, the number of very elderly patients admitted to the ICU with acute illnesses is increasing. [1][2][3] A study in Australia and New Zealand found an annual increase of 5.6% in the number of ICU patients over 85 y.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that younger women are more likely to opt for surgical management of prolapse; however, our study suggests that these factors influence physicians' counseling as well [8,24]. Older women and those with Medicare may have more comorbidities that make them poorer surgical candidates [25][26][27]; therefore, physicians may be more apt to offer them conservative management. However, in our study cohort, all women ultimately had surgery for prolapse and the proportion of women with ASA Class ≥3 was the same among women with and without a pessary offer.…”
Section: Commentmentioning
confidence: 67%